2006
DOI: 10.1111/j.1083-6101.2002.tb00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Internet Adoption in Macao:

Abstract: Based on the data from a telephone survey of 868 Macao residents conducted in Macao with 330 Internet users and 538 non-users, this paper examines the characteristics of the users and non-users in terms of their demographics, assessments on media credibility, family functioning, media use, and perceived values of the Internet. Drawing from the literature of diffusion, expectancy-value and media substitution theories, it investigates the relations between Internet use and its potential predictors. The results c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…But this disproportionately low use of the Internet by women is in line with previous findings. In a survey of Macau residents, Internet users were more likely to be male (Cheung, 2001). In a survey of Indian Internet users, it was found that even when women do start using cybercafés, they use them less often and for shorter duration per session than men (Haseloff and Ghadially, 2007).…”
Section: Computer Education Use and Empowermentmentioning
confidence: 99%
“…But this disproportionately low use of the Internet by women is in line with previous findings. In a survey of Macau residents, Internet users were more likely to be male (Cheung, 2001). In a survey of Indian Internet users, it was found that even when women do start using cybercafés, they use them less often and for shorter duration per session than men (Haseloff and Ghadially, 2007).…”
Section: Computer Education Use and Empowermentmentioning
confidence: 99%
“…209–222). To be more specific, this article takes the most popular social media in Macao, Facebook—especially the top 10 popular Facebook group pages—as the ethnographic field for fieldwork participant observation (Cheong, Chang & Lam, 2011), with 158 ethnographic interviews on university students, and 7 in-depth interviews on influential actors, founders or administrators of the Facebook groups. The ethnographic interviewees were mainly university students from University of Macau over the course of three years, namely 2012, 2013 and 2014.…”
Section: Immaterials Labour In the Digital Capitalismmentioning
confidence: 99%
“…Studies of internet adoption in Macao, China and India all found that adopters of this new technology were in the higher socioeconomic brackets of their respective societies, and resided in urban areas (Kshetri, 2002;Cheong, 2002).…”
Section: Income/wealthmentioning
confidence: 99%
“…Living in urban areas has been found to be important for determining technology adoption probably because the bulk of the infrastructure that supports these technologies is found in these areas. This occurs often because it is more profitable for providers of infrastructure to supply to the "more lucrative" urban dwellers (Schirmer and Goetz, 1997;Kshetri , 2002;Cheong, 2002, UNDP, 1999.…”
Section: Other Factorsmentioning
confidence: 99%